Sex differences in the association of risk factors for heart failure incidence and mortality. Issue 3 (31st July 2019) - Sillars, Anne; Ho, Frederick K; Pell, Gill P; Gill, Jason M R; Sattar, Naveed; Gray, Stuart; Celis-Morales, Carlos
Abstract : Background: There are known risk factors associated with the development of heart failure (HF), but it is not fully understood whether these differ by sex. Objectives: To investigate sex differences in risk factors for HF incidence and mortality. Methods: 468 941 participants (55.9% women, age range 37–73 years) were included. Established CVD risk factors (hypertension, hypercholesterolaemia, diabetes type 1 and 2, adiposity, smoking, physical activity and poor diet) and novel risk factors (grip strength, fitness, TV viewing and sleep duration) were the exposures of interest. HF incidence and mortality were the outcomes. Results: Over a mean follow-up of 9.0 years, 1812 participants developed HF and 763 died due to HF. Women with type 1 diabetes (T1DM), type 2 diabetes (T2DM), hypertension, hypercholesterolaemia, low levels of physical activity and fitness, low strength, high levels of TV viewing, sleep duration <7 hours/day, smokers; those who were underweight and who were obese, had high body surface area and those who drink >14 units of alcohol were at higher risk of HF incidence. However, in women T2DM, hypercholesterolaemia, >3 hours/day of TV and sleep <7 hours/day, low level of physical activity and high level of TV viewing were more strongly associated with HF incidence compared with men. Conclusion: Several modifiable risk factors (in particular diabetes) appear more strongly associated with HF in women compared with men. The relevance of these findings to HF characteristics and future outcomes needs to be established.